HUMAN RESOURCES INFORMATION SYSTEM TO IMPROVE EMPLOYEE PERFORMANCE - Hikmawan, Try; Budi Santoso (Dinasti Publisher, 2020)
Today employee performance is a fundamental element for the progress of the institution. Along with the changing times demanded in increasing employee performance in order to achieve the objectives to be achieved. The discussion of this study regarding the decline in employee performance is characterized by a decrease in the percentage of achievement of work program targets. In this study, there are two variables, namely human resources information system variable (X) and employee performance variable (Y). This study aims to determine the effectiveness of human resources information system and the level of employee performance. This research method uses descriptive method using the type of explanatory survey research. Data collection techniques used were interviews and questionnaires that used a rating scale measurement scale. Data analysis techniques using simple regression analysis. The population in this study is employees. Based on the results of the study, showed that the respondents' perceptions of performance appraisal in the effective category were in the very high category. Hypothesis testing shows that human resources information system has a positive and significant influence on employee performance